The Hermeneutics of Values in the Novel A Portion of Chicken Noodles Before Dying as a Source of Existential Counseling Intervention - Rahmawati; Budi Purwoko; Evi Winingsih; Bakhrudin All Habsy (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Many individuals experience confusion regarding the meaning and purpose of life due to the pressure of social comparison, making it difficult for them to fully understand themselves. This study aims to analyze the existential values in the novel Seporsi Mie Ayam Sebelum Mati as a source of existential counseling intervention. The study was conducted using Gadamer's hermeneutic approach and data analysis using the Miles and Huberman model, allowing for in-depth interpretation of the characters' experiences and the existential values contained therein. The results show that freedom, suffering, hope, openness, and responsibility are the main themes in the characters' journeys to find the meaning of life. Relevant to existential counseling interventions, it can strengthen counselors in helping clients become more aware of their life choices, accept themselves, find their direction in life, manage emotional wounds, and take ownership of their lives. These findings confirm that literary works can function as a reflective medium and help clients understand the meaning of life more deeply. This study strengthens the practice of existential counseling by providing literary narratives as intervention materials. This approach allows counselors to guide individuals in connecting personal experiences with existential values, so that clients can live lives more authentically, responsibly, and meaningfully. Thus, this research opens up opportunities for the development of narrative-based creative counseling methods, which can be adapted in various educational or psychological contexts.